MULTIPARTICULATE FLOATING DRUG DELIVERY SYSTEM OF ANAGLIPTIN: DESIGN AND OPTIMIZATION FOR ITS EFFICACY IN MANAGEMENT OF METABOLIC SYNDROME - MISHRA, RAKESH V.; DHOLE, SHASHIKANT N. (International Journal of Applied Pharmaceutics, 2019)
Objective: The present research aims to design and optimize gastroretentive floating pellets of anagliptin (a dipeptidyl peptidase-4 inhibitor), so as to reduce P-Glycoprotein (PGP)–mediated efflux in the intestine hence to improve oral bioavailability. Methods: The drug-containing core pellets were prepared by extrusion and spheronization process followed by subsequent coating with three successive layers i.e. Eudragit RS 100, sodium bicarbonate (NaHCO3): hydroxypropyl methylcellulose E5LV (HPMC E5LV) and Eudragit RL 100 using fluidized bed processor. A 3 level 3 factor box-behnken design was adopted to investigate the effect of Eudragit RS 100, NaHCO3: HPMC E5LVand Eudragit RL 100 on floating lag time and drug release at 10 h. Desirability function under numerical optimization technique was used to identify the optimum formulation. Results: The study reveals the significant effect of the amount of NaHCO3 and coating level of polymers on floating lag time and drug release. The optimum system could float within 4 min and exhibited more than 85% drug release in 10 h. The pharmacokinetic study conducted in male Wistar rats indicated 2.51 fold increase in relative bioavailability of optimized formulation compare to anagliptin drug. Formulated anagliptin pellets were evaluated in cafeteria diet-induced metabolic syndrome model in male Wistar rats. Anagliptin floating pellets treatment compared to cafeteria diet group significantly inhibited increase in body weight (238.79±2.52 g vs. 277.98±3.69 g, P<0.001), calorie intake (2283.99 kcal vs. 3086.05 kcal, P<0.05) and serum levels of total cholesterol (95.19±0.61 mg/dl vs. 110.04±1.31 mg/dl, P<0.01), triglycerides (96.12±1.25 mg/dl vs. 105.99±1.29 mg/dl, P<0.01) while high-density lipoproteins levels were improved (42.15±0.92 mg/dl vs. 30.92±0.77 mg/dl, P<0.01) indicated its hypophagic and anti-hyperlipidemic effects. Conclusion: The gastroretentive floating pellets of anagliptin was obtained and could be a promising technique to deliver anagliptin with improved bioavailability in the management of the metabolic syndrome.